5 Mental health-related presentations to emergency medical services in victoria, australia. (21st May 2017) - Andrew, E; Roggenkamp, R; Nehme, Z; Cox, S; Smith, K
Abstract : Aim: Recent increases in demand for mental health services have not been matched with community resources, resulting in increased demand on emergency medical services (EMS). We sought to describe the clinical profile, demand patterns and care provided to mental health patients accessing EMS in ?Victoria, Australia. Methods: We conducted a retrospective observational study of cases occurring between January and December 2015. Computer Aided Dispatch and electronic patient care record data were extracted from the Ambulance Victoria data warehouse. Characteristics of mental health presentations were described using descriptive statistics. Results: Of the total 504, 676 EMS attendances, 48 041 (9.5%) were mental health-related. Additionally, 4708 mental health-related secondary triages were included, representing 6.6% of the Victorian secondary triage caseload. Emergency mental health patients were younger and more often female than other patients attended by EMS (p<0.001). Most mental health patients were transported to hospital (74.4%), however paramedics provided treatment to significantly fewer mental health patients than other emergency patients (12.4% vs. 50.3%, p<0.001). In mental health patients ≤15 years, the most common presentations involved social/emotional issues, while for patients aged ≥65 years, the most common presentation was anxiety. In patients undergoing secondary triage, 52.5% were frequent callers or anxiety presentations. A total of 27.7% of triaged patients were referred to an alternative service, while 24.6% were managed as per a care plan. Conclusion: For mental health-related cases, EMS were predominantly utilised as a transport mechanism rather than for active medical intervention. The role of alternative services in provision of care for mental health patients requires further investigation. Conflict of interest: None declared. Funding: None declared.